Teacher-Parent Collaboration in Strengthening Character Education in the Digital Era at the Elementary School Level - Ifrah Muliyani E. Pulungan; Saadah Dalimunthe; Tuti Alawiyah Matondang; Hamka (Al-Qalam Institute, 2025)
Character education at the elementary level has grown harder to sustain as children spend more of their lives on screens, and neither the school nor the family can shoulder the task alone. This study examines how teachers and parents collaborate to strengthen character education in the digital era, along with the factors that support and weaken that cooperation. The research used a qualitative descriptive approach at one elementary school, drawing on in-depth interviews with two teachers and three parents, participant observation, and document analysis, with findings verified through triangulation of source, technique, and time. Analysis followed the interactive stages of data reduction, data display, and conclusion drawing. Four collaborative practices emerged. Teachers and parents kept up steady two-way communication through real-time channels such as class messaging groups, supervised children's device use jointly across the classroom and the home, habituated character values through daily routines anchored in school rituals and home records, and modeled the digital conduct they expected children to adopt. The strength of the collaboration lay in its consistency, since a child met the same standard enforced in more than one setting. The main obstacle was not parental unwillingness but limited parental fluency with the platforms their children use. The study implies that shared digital supervision deserves recognition as a distinct area of home and school partnership, and it recommends that schools formalize collaboration through joint policy and invest in parents' digital literacy.